Estilos de enseñanza y estilos de aprendizaje en estudiantes de nivel primaria de la Institución Educativa N° 62419 Santa Mercedes de Pillingue Alto Amazonas 2024 - Cahuaza Huansi, Francisco (2024)
The main objective of this study was to determine the relationship between teaching styles and learning styles of primary level students of the Educational Institution No. 62419 Santa Mercedes de Pillingue, Alto Amazonas, in the year 2023. The study is of a basic type, with a non-experimental, transactional and correlational design. The population consisted of 43 primary level students. The survey technique was used, applying a questionnaire for the teaching styles variable and the CHAEA-Junior questionnaire for the learning styles variable. The results showed a significant and moderate relationship between teaching styles and learning styles (Rs= 0.582, p<0.01). It is concluded that there is a significant relationship between teaching styles and learning styles in the evaluated students, with significant correlations highlighted in multiple combinations of styles, especially between the structured teaching style and the pragmatic learning style.